2020
DOI: 10.1002/jper.20-0266
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periodontal status, oral inflammatory load, and systemic inflammation are associated with low infant birth weight

Abstract: Background Periodontal disease and pregnancy outcomes have been claimed to be associated with conflicting reports. The purpose of this study was to prospectively examine the association between maternal periodontal status, oral inflammatory load and serum C‐ reactive protein (CRP) level, and infant birth weight. Methods A total of 156 pregnant women (age 26.62 ± 3.93 years) within the gestational age group of 13 to 32 weeks participated in this cross‐sectional study. Oral inflammatory load (OIL) was assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
(55 reference statements)
0
12
0
1
Order By: Relevance
“…In addition, in animal studies, it was also shown that the serum levels of IFN-γ, IL-1β, IL-6, and IL-8 in premature mice with oral infection were significantly increased ( 41 , 42 ). Equally, serum C-reactive protein concentrations were significantly increased to pregnant women with periodontal disease and were positively associated with the occurrence of low birth weight and pre-eclampsia ( 18 , 43 ). In summary, all of the above studies showed that, periodontal disease can increase the levels of inflammatory mediators both in the oral cavity and throughout the body, causing the systemic inflammatory response during pregnancy, and eventually leading to preterm birth, low birth weight and pre-eclampsia.…”
Section: Mechanisms Related To Periodontal Disease Leading To Adverse...mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, in animal studies, it was also shown that the serum levels of IFN-γ, IL-1β, IL-6, and IL-8 in premature mice with oral infection were significantly increased ( 41 , 42 ). Equally, serum C-reactive protein concentrations were significantly increased to pregnant women with periodontal disease and were positively associated with the occurrence of low birth weight and pre-eclampsia ( 18 , 43 ). In summary, all of the above studies showed that, periodontal disease can increase the levels of inflammatory mediators both in the oral cavity and throughout the body, causing the systemic inflammatory response during pregnancy, and eventually leading to preterm birth, low birth weight and pre-eclampsia.…”
Section: Mechanisms Related To Periodontal Disease Leading To Adverse...mentioning
confidence: 96%
“…Likewise, a hospital-based cross-sectional case-control study suggested that the presence of postpartum maternal periodontitis and its severity remained independent risk factors for preterm birth in the presence of antepartum smoking habits and routes of delivery ( 17 ). A cross-sectional study recording clinical periodontal parameters and assessing serum C-reactive protein levels confirmed that poor maternal periodontal status, increased oral inflammatory burden and increased systemic inflammation had an adverse effect on infant birth weight ( 18 ). In addition, it was suggested that periodontal infection could exacerbate the progression of pre-eclampsia, and periodontal disease was considered to be one of the risk factors for pre-eclampsia ( 19 , 20 ).…”
Section: The Association Between Periodontal Disease and Adverse Preg...mentioning
confidence: 97%
“…Evidence suggests an association between these pro- and anti-inflammatory markers and gestational outcomes, including preterm and low birth weight neonates in healthy pregnant women [ 18 ] and among those with periodontitis [ 19 ]. In a prospective study conducted in Brazil, pregnant women in the higher tertile of the CRP trajectory gave birth to infants with a lower mean birth weight Z-score than pregnant women in the first/second CRP tertiles [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to scienti c literature, bacteria plaque control during pregnancy and more complex periodontal treatments such as scaling and root planning, can contribute to decreased gingival in ammation [18], improved quality of life during pregnancy [19] and reduce the prevalence of adverse pregnancy outcomes in women with periodontal disease [20]. Also, early interventions in healthy and high-risk pregnant women can play a key role in the preservation of adequate periodontal health throughout pregnancy [21].…”
Section: Introductionmentioning
confidence: 99%